L’usage des TIC par les indésirables - Rafik Arfaoui (Netcom)
Restrictions on the movement of persons imposed by the Northern States are at the root of irregular migratory flows. These flows are not exclusively South-North, they can be oriented South-South. During their crossing, migrants face several administrative, political and social obstacles. Information and Communication Technologies (ICTs) are present throughout their migratory pathway which refers both to a spatial and social dimension (the spaces traveled by migrants and the social positions they have occupied throughout their life in mobility). ICTs thus play a central role in facilitating the passage of political and administrative barriers in the North and the South. The use of ICTs is, on the one hand, an essential element for the construction and preservation of the social link in the countries of departure, transit and reception and contributes, on the other hand, to the diffusion of a migratory imaginary, which is an issue for the structural change of the migratory project. The analysis of the use of ICTs by migrants makes it possible to highlight different dynamics linked to the issue of international migration by constantly questioning the relationship between man and territory.